The Impact of Different Types of Auditory Warnings on Working Memory - Lei, Zhaoli; Ma, Shu; Li, Hongting; Yang, Zhen (Frontiers in Psychology, 2022)
Auditory warnings have been shown to interfere with verbal working memory. However, the impact of different types of auditory warnings on working memory tasks must be further researched. This study investigated how different kinds of auditory warnings interfered with verbal and spatial working memory. Experiment 1 tested potential interference of auditory warnings with verbal working memory. Experiment 2 tested potential interference of auditory warnings with spatial working memory. Both experiments used a 3 × 3 mixed design: auditory warning type (auditory icons, earcons, or spearcons) was between groups, and task condition (no- warning, identify-warning, or ignore-warning) was within groups. In Experiment 1, earcons and spearcons but not auditory icons worsened the performance on the verbal serial recall task in the identify-warning condition, compared with that in the no-warning or ignore-warning conditions. In Experiment 2, only identifying earcons worsened the performance on the location recall task compared with performance without auditory warnings or when auditory warnings were ignored. Results are discussed from the perspective of working memory resource interference, and their practical application in the selection and design of auditory warning signals is involved.